MEDICINAL PROPERTIES OF PLANTAGO MAJOR L. (Multidisciplinary Journal of Science and Technology, 2023)
This article provides information on the appearance and geographical distribution of the plant (Plantago major L.), its uses, chemical composition and uses, and its specific medicinal properties.